(untitled) (Scientific journal of the Fergana State University, 2024)
Translating Uzbek literature to English presents several unique challenges. The vast differences in grammatical structure and syntax between the two languages, the intricate cultural nuances embedded in Uzbek idioms and expressions, and the scarcity of high-quality translations are major hurdles. Additionally, the agglutinative nature of the Uzbek language, which heavily relies on suffixes, poses difficulties in maintaining the original meaning and flow when converting to English. The limited availability of linguistic resources and the need to convey appropriate levels of politeness and formality further complicate the translation process. Overcoming these challenges requires a deep understanding of both languages and cultures, as well as creative and flexible translation strategies.